Publisher Correction: Precision and accuracy of single-molecule FRET measurements—a multi-laboratory benchmark study. (November 2018) - Hellenkamp, Björn; Schmid, Sonja; Doroshenko, Olga; Opanasyuk, Oleg; Kühnemuth, Ralf; Adariani, Soheila; Ambrose, Benjamin; Aznauryan, Mikayel; Barth, Anders; Birkedal, Victoria; Bowen, Mark; Chen, Hongtao; et al.
This paper was originally published under standard Springer Nature copyright. As of the date of this correction, the Analysis is available online as an open-access paper with a CC-BY license. No other part of the paper has been changed.